2. From Efficiency to Resilience - Halme, Minna; Furman, Eeva; Apajalahti, Eeva-Lotta; Jaakkola, Jouni; Linnanen, Lassi; Lyytimäki, Jari; Mönkkänen, Mikko; Salonen, Arto O.; Soini, Katriina; Siivonen, Katriina; Toivonen, Tuuli; Tolvanen, Anne (Open Book Publishers, 2021)
The COVID-19 pandemic has revealed the vulnerability of current socio-economic systems and thrown into question the dominant global paradigm geared towards short-term financial efficiency. Although it has been acknowledged for several decades that this paradigm has detrimental impacts on the climate, the environment and global welfare, the pandemic has now offered a grim ‘rehearsal round’ for more serious crises that are to come with the accelerating climate emergency, loss of biodiversity and growing human inequalities. Along with worsening climate change, there are looming risks for mass migrations and armed conflicts as habitats capable of supporting human wellbeing become scarce, such as through the loss of potable water, an increasing lack of suitable land for agriculture, or the rise of unliveable temperatures. Although the COVID-19 pandemic has temporarily decreased some of the climate impacts, e.g. in the energy and transportation sectors, it has at the same time accelerated several global welfare problems. In this chapter, we claim that the way out of the crisis scenario is to replace the dominant efficiency paradigm with a resilience paradigm. Against the backbone of the key societal systems outlined in the Global Sustainable Development Report (GSDR 2019), we show how the pursuit of narrowly-defined efficiency hampers present and future sustainability, and chart some key actions on the path to transforming these systems towards resilience.
Keywords: pandemics; COVID-19; sustainability